2021
DOI: 10.1099/ijsem.0.004669
|View full text |Cite
|
Sign up to set email alerts
|

Protaetiibacter larvae sp. nov. and Agromyces intestinalis sp. nov., isolated from the gut of larvae of Protaetia brevitarsis seulensis, reclassification of Lysinimonas yzui as Pseudolysinimonas yzui comb. nov. and emended description of the genus Pseudolysinimonas

Abstract: Two bacterial strains, FWR-8T and CFWR-9T, were isolated from the gut of larvae of Protaetia brevitarsis seulensis that were raised at the National Institute of Agricultural Sciences, Wanju-gun, Republic of Korea. Both strains were strictly aerobic, Gram-stain-positive and non-motile. Strain FWR-8T possessed the highest sequence similarity (98.7 %) to that of Protaetiibacter intestinalis 2DFWR-13T and the phylogenetic tree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The genome of strain CFWR-12 T has been found to harbour genes associated with virulence, resistance to antibiotics and multidrug resistance. Its nearest neighbour type strain and its closely related species were also been reported to contain genes coding for metal and antibiotic resistance as well as for beta-lactamase and multidrug resistance efflux pumps [15]. This is highly significant at this point as the source of strain CFWR-12 T in the current study and A.…”
Section: Genome Featuresmentioning
confidence: 81%
See 2 more Smart Citations
“…The genome of strain CFWR-12 T has been found to harbour genes associated with virulence, resistance to antibiotics and multidrug resistance. Its nearest neighbour type strain and its closely related species were also been reported to contain genes coding for metal and antibiotic resistance as well as for beta-lactamase and multidrug resistance efflux pumps [15]. This is highly significant at this point as the source of strain CFWR-12 T in the current study and A.…”
Section: Genome Featuresmentioning
confidence: 81%
“…Strain CFWR-12 T showed the highest sequence similarity to Agromyces intestinalis KACC 19306 T (99.0 %; NCBI Accession MT367292) and Agromyces protaetiae FW100M-8 T (97.9 %; NCBI Accession MK490987) both of which were previously isolated from the larval gut of PBS [4, 15]. Phylogenetic analysis showed that strain CFWR-12 T formed a robust clade with Agromyces intestinalis KACC 19306 T ().…”
Section: S Rrna Gene Phylogenymentioning
confidence: 99%
See 1 more Smart Citation
“…The Gram-stain type was determined using the method described by Beveridge et al [20]. Growth at various temperatures was determined at 4-45 °C (4,10,15,20,25,28,30,35,37,40,42 and 45 °C) in R2A broth. Tolerance of NaCl was tested by growing the isolates in R2A broth supplemented with 0-5.0 % (w/v) NaCl at intervals of 0.5 %.…”
Section: Morphological Physiological and Biochemical Characterizationmentioning
confidence: 99%
“…Species in the genus Agromyces exist in many habitats through the pedosphere, including forest soils, farm soils, plateau soils, stones and sea sediments [1,2,[6][7][8][9][10][11][12][13][14][15][16]. Additionally, some of the species of the genus Agromyces are found in symbiosis with other organisms, such as rhizospheres [17][18][19][20], gut of larva [21,22] or in the above-ground part of plants [23]. There are also reports on some species of the genus Agromyces taking part in plant xylems natural degradation [24] or sea food fermentation [25].…”
mentioning
confidence: 99%